Technological Development and Agricultural Revolutions in India: A Case Study (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Various government policy, schemes, grants etc. have a considerable impact on the Indian economy at various time. But the most revolutionary event among them was the revolution in agriculture. As a result of this revolution, India’s place on the world agricultural map rose to a high place. India’s food problem is almost solved. Increases India’s food security. Green revolution (food grains production), Blue revolution (fish production), White revolution (milk production), Yellow revolution (oilseed production), Gray revolution (fertilizer production) etc. are important in agricultural revolution. The invention of advanced research technology related to agriculture, the use of modern machinery, through changing the character of the land etc. the production in the field of agriculture will increase dramatically. As a result, the domestic demand met as well as earning a lot of foreign exchange through exports. However, due to lack of proper government policy, the impact of the agricultural revolution was not felt by all the states of India, Indian states like Gujrat, Punjab, Uttar Pradesh, Haryana, West Bengal have developed rapidly, but other states like Bihar Tripura, Jharkhand, Chhattisgarh etc. have not had the success of the agricultural revolution. However, at present, efforts are being made to solve this problem through like the second Green Revolution, Evergreen Revolution etc.